Primary screening of the biological activity of heterocyclic aminoderivatives of 2,3-dichloro-1,4-naphtoquinone - Polish, Nataliia; Voitsakhivska, Olha; Marintsova, Nataliia; Zhurakhivska, Lesya; Novikov, Volodymyr; Bohza, Serhii (ScienceRise: Pharmaceutical Science, 2019)
The aim. Check the antimicrobial and fungicidal activity of 2,3-dichloro-1,4-naphthoquinone aminopyrazole derivatives and predict their severity of toxicity to rats. Materials and methods of the research. The antimicrobial activity of heterocyclic amino derivatives of naphthoquinone 3a-d was studied by diffusion of the substance into agar on solid nutrient medium and by serial dilution. Acute rodent toxicity was determined by the QSAR simulation method implemented in GUSAR software. Results. In the work, the antimicrobial and fungicidal activities of new heterocyclic amino derivatives of naphthoquinone were studied, as well as the in silico determination of their acute toxicity for rats was carried out using four types of substance administration. Conclusions. The study of aminopyrazole derivatives of naphthoquinone revealed the compounds exhibiting high antimicrobial activity against the Candida tenuis test culture, namely: 2-chloro-3-((1-methyl-1H-pyrazol-4-yl) amino) naphthalene-1,4-dione (3a) and 2-chloro-3 - ((1-methyl-1H-pyrazol-3-yl) amino) naphthalene-1,4-dione (3b). All the synthesized compounds were found to exhibit selective bacterio- and fungistatic activity. QSAR determined the non-toxic compound 3c in the intraperitoneal route of administration, as well as the non-toxic compound 3d in the subcutaneous route of administration